Can varying the number of teams in a shift schedule constitute a preventive strategy? - Hans Jeppe Jeppesen; Magnar Kleiven; Henrik Bøggild (Universidade de São Paulo, 2004)
OBJECTIVE: The study examines the implications for shiftworkers of applying different numbers of teams in the organization of shiftwork. METHODS: The participating operators came from five different companies applying continuous shift rotation systems. The companies shared the same product organization and a common corporate culture belonging to the same multinational company. Each company had a shift system consisting of four, five or six teams, with the proportion of shifts outside day work decreasing as the number of teams increased. Questionnaire and documentary data were used as data sources. RESULTS: Operators in systems with additional teams had more daywork but also more irregular working hours due to both overtime and schedule changes. Operators using six teams used fewer social compensation strategies. Operators in four teams were most satisfied with their work hours. Satisfaction with the time available for various social activities outside work varied inconsistently between the groups. CONCLUSIONS: In rotating systems the application of more teams reduces the number of shifts outside day work. This apparent improvement for shiftworkers was counteracted by a concomitant irregularity produced by greater organizational requirements for flexibility. The balance of this interaction was found to have a critical impact on employees. OBJETIVOS: Investigar as implicações para trabalhadores em turnos do uso de um número distinto de turmas de trabalho na organização dos turnos. MÉTODOS: Participaram do estudo operadores de cinco empresas que usavam sistemas contínuos de turnos alternantes. As empresas tinham em comum a organização de produtos e cultura empresarial e pertenciam a uma mesma empresa multinacional. Cada uma das empresas tinha um sistema de turnos que compreendia quatro, cinco ou seis turmas de trabalho, sendo que a proporção de turnos fora dos horários diurnos diminuía à medida que aumentava o número de turmas. Foram usados dados de questionários e documentação como fontes de pesquisa. RESULTADOS: Os operadores de sistemas com turmas extras apresentaram uma quantidade maior de trabalho diurno, assim como mais horas irregulares de trabalho em decorrência de horas extras e mudanças de horário. Os operadores que contavam com seis turmas usaram menos recursos de compensação social. Os que trabalharam com quatro turmas ficaram mais satisfeitos com os horários de trabalho. A satisfação com o tempo disponível para diversas atividades sociais fora do trabalho variou de modo inconsistente entre as turmas estudadas. CONCLUSÕES: Nos sistemas com turnos rodiziantes, o uso de um número maior de turmas reduz o número de turnos não-diurnos. Esta aparente vantagem aos trabalhadores em turnos foi neutralizada pela concomitante irregularidade resultante de maiores exigências organizacionais para permitir flexibilidade. Verificou-se que o equilíbrio desta interação teve um impacto fundamental sobre os trabalhadores.